Mengurai Efektivitas Bauran Promosi Dalam Mendorong Kinerja Penjualan: Studi Pada PT ABC Kota Bogor - Endang Silaningsih; Giska Wafiq Azizah Setiawan (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the implementation of the promotion mix at PT ABC Bogor and to evaluate the level of integration and effectiveness of its promotional activities in supporting marketing performance. The research employs a qualitative approach using a case study method. Data were collected through in-depth interviews, observation, and documentation, and analyzed descriptively based on the concepts of promotion mix and Integrated Marketing Communication (IMC). The findings reveal that PT ABC has structurally implemented all elements of the promotion mix, including advertising, sales promotion, personal selling, public relations, and direct marketing. However, the effectiveness of these activities has not been fully optimized due to weak strategic integration and inconsistent messaging across promotional elements. Promotional activities tend to be conducted in a fragmented and tactical manner, resulting in marketing messages that are insufficient to build strong and sustainable brand perceptions. In addition, the utilization of digital media and direct marketing is not yet supported by an integrated customer database system. This study contributes to the marketing literature by highlighting that the main challenge in promotion mix implementation among medium-sized firms lies not in the absence of promotional instruments, but in the gap between the IMC concept and its operational practice. The findings emphasize the critical role of strategic integration and message consistency in enhancing the effectiveness of promotional activities and overall marketing performance.